G-Theory of Group Rings for Groups of ElementsAbelian p-Groups (2009)
The formula for the G— theory of the group ring of a finite group G given by H. co. Lenstra is shown to be valid for groups of elementary abelian P— groups. Keywords: Group rings , G— theory